Shifting N and P concentrations and stoichiometry during autumn litterfall: Implications for ecosystem monitoring. (August 2019) - See, Craig R.; Yanai, Ruth D.; Fahey, Timothy J.
Highlights: Recently abscised leaf litter declined throughout the litterfall season. P was reduced more than N as a proportion of the first collection. Litterfall N:P ratios increased throughout the season. Intra-seasonal change in litter nutrients impact estimates of nutrient fluxes. Abstract: Leaf litterfall nutrient concentrations and their ratios are a common indicator of site nutrient status and a critical component of many ecosystem calculations. Concentrations of nitrogen (N) and phosphorus (P) in leaf litter are related to foliar concentrations, but they are reduced by nutrient resorption during senescence. Although nutrient resorption occurs gradually during the autumn in winter-deciduous species, no study to date has assessed how the timing of litter collection affects estimates of nutrient concentration. To quantify the importance of this effect we analyzed the nutrient concentrations of leaf litter collected weekly in two northern hardwood sites at the Hubbard Brook Experimental Forest for three dominant tree species: Acer saccharum, Betula alleghaniensis, and Fagus grandifolia . Both N and P concentrations declined significantly during the litterfall season in all species ( p  < 0.001). Because P concentrations declined proportionately more than N concentrations, leaf litter N:P ratios increased throughout the season ( p  < 0.001), likely reflecting the ordered breakdown of the different cellular constituents containing these nutrients. Our results suggest that sampling senesced leaf tissue at a single point in time leads to biased estimates of nutrient concentrations, stoichiometry, and litterfall and resorption fluxes. This bias is likely greater for P than for N.